Motivations and Expectations of Students in a University Program for Older Adults Towards Online Learning - Herrada, Rosario Isabel (2025)
Objective. The University Programmes for Older Adults, aimed at people over 55 years of age, include among their objectives educational and social inclusion through lifelong learning. The health crisis caused by COVID-19 led some of these programmes to teach in virtual mode in the 2020-2021 academic year. This study analyzes the impact of this change on students' motivations and expectations towards the online learning process. Methodology. A mixed qualitative and quantitative methodology is used so that the 230 students enrolled in the University of Almeria's Senior University are asked to answer a structured questionnaire on these motivations and expectations, so that a total of 62 students voluntarily agreed to participate in the study. The collection of information is articulated through an online questionnaire validated by triangulation and expert judgement and various official documentation of the university program for seniors. Results. The existence of resistance to the substitution of face-to-face teaching by virtual teaching is detected, although the majority of the students would continue the training process the following year, regardless of the teaching mode offered. The heterogeneity of the group of students, who avoid being pigeonholed as a homogeneous group, is also evident, as can be seen from the motivations, perceptions, and expectations about the learning process that they state. Conclusions. The students assume that distance learning is an exceptional circumstance linked to the pandemic, and although there is resistance to online versus face-to-face teaching, they show great interest in the training program and wish to continue with it.